Coffee and tea consumption and dementia risk: The role of sex and vascular comorbidities - Kuan-Chu Hou; Yen-Ching Chen; Ta-Fu Chen; Yu Sun; Li-Li Wen; Ping-Keung Yip; Yi-Min Chu; Jeng-Min Chiou; Jen-Hau Chen (Journal of the Formosan Medical Association)
Background: Coffee and tea consumption has been linked to dementia. However, it remained unknown how sex and vascular risk factors modify the association. We aimed to investigate the association of coffee and tea consumption with dementia and whether sex and vascular comorbidities modified the association. Methods: We included 278 elderly patients with Alzheimer's disease (AD) and 102 patients with vascular dementia (VaD) from three hospitals; controls (N = 468) were recruited during the same period. We collected the frequency and amount of coffee and tea consumption and the presence of vascular comorbidities. The multinomial logistic regression model was utilized to evaluate the association of coffee and tea consumption with dementia, stratified by sex and vascular comorbidities. Results: Different combinations and quantities of coffee and tea consumption protected against AD and VaD. Consumption of ≥3 cups of coffee or tea per day was protective against AD [adjusted odds ratio (aOR) = 0.42; 95% confidence interval (CI) = 0.22–0.78)] and VaD (aOR = 0.42; 95% CI = 0.19–0.94). Stratified analyses showed that the protective effects of a higher quantity of coffee and tea against AD were more pronounced among females and individuals with hypertension. Consumption of either coffee or tea was associated with a decreased risk of VaD among diabetic participants (aOR = 0.23; 95% CI = 0.06–0.98). Hyperlipidemia modified the association of coffee or tea consumption on the risk of AD and VaD (both Pinteraction < 0.01). Conclusion: The risk of AD and VaD was lower with increased consumption of coffee and tea; the impact differed by sex and vascular comorbidities including hypertension, hyperlipidemia, and diabetes.